TINJAUAN YURIDIS KEDUDUKAN INTERNATIONAL CRIMINAL COURT (ICC) TERHADAP INVESTIGASI KASUS PELANGGARAN HAM BERAT PALESTINA DAN ISRAEL - Yusuf Hofni Junior Kilikily (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2025)
This study discusses the juridical review of the status of the International Criminal Court (ICC) in relation to the investigation of gross human rights violations in Palestine and Israel. The objectives of this research are: (1) to understand the regulatory framework concerning the International Criminal Court's (ICC) role in resolving investigations of gross human rights violations based on the Rome Statute of 1998, and (2) to analyze the ICC's position concerning the investigation of gross human rights violations in Palestine and Israel. This study employs a descriptive normative legal research method with a statutory, historical, and conceptual approach. The findings indicate that (1) the International Criminal Court (ICC) plays a crucial role in resolving cases of gross human rights violations under the Rome Statute, possessing the specific authority to initiate proprio motu investigations independently into gross human rights violations in Palestine, in accordance with Article 15 of the Rome Statute. Furthermore, (2) the ICC's position in the investigation process concerning Israel is that of a primary court; due to the inability and unwillingness of Israel's national courts to address the alleged cases involving Benjamin Netanyahu, the ICC has assumed jurisdiction. However, the implementation of the investigation process faces obstacles and challenges, primarily the intervention of the United Nations Security Council, which can defer the investigation of gross human rights violations in Palestine and Israel, as stipulated in Article 16 of the Rome Statute.